Free Convection Heat Transfer in Composite Enclosures with Porous and Nanofluid Layers - Abeer Alhashash (Advances in Mathematical Physics)
This work conducts a numerical investigation of convection heat transfer within two composite enclosures. These enclosures consist of porous and nanofluidic layers, where the porous layers are saturated with the same nanofluid. The first enclosure has two porous layers of different sizes and permeabilities, while the second is separated by a single porous layer. As the porous layer thickness approaches zero, both enclosures transition to clear nanofluid enclosures. The study uses the Navier–Stokes equations to govern fluid flow in the nanofluid domain and the Brinkman–Forchheimer extended Darcy model to describe flow within the saturated porous layer. Numerical solutions are obtained using an iterative finite difference method. Key parameters studied include the porous thickness (0.0≤S≤1.0), the nanoparticle volume fraction (0.0≤ϕ≤0.05), the thermal conductivity ratio (0.5≤Rk≤10), and the Darcy number (10−5≤Da≤10−2). Key findings include the observation that the highest heat transfer is achieved at the highest concentration, regardless of the porous layer configuration, permeability value, or thermal conductivity ratio. Specifically, an augmentation in values of Nu―I up to 22% is obtained as concentration is adjusted from 1% to 5%. Similarly, an augmentation in values of Nu―II up to 25% is obtained as concentration is adjusted from 1% to 5%.